Eksistensi bangunan gaya kolonial Belanda di kawasan Kayutangan, Kota Malang pada tahun 1900-2021 - Khamaliyah Nur Erine; Sakafitri Rimasari; Ari Sapto (Historiography: Journal of Indonesian History and Education, 2022)
The history of the city of Malang has a long journey until the presence of the city of Malang is rapidly as it is today. Judging from its history, in 1914 the Kayutangan area to the Malang city square was used as the center of Malang city at that time. This is because the geographical location of Kayutangan is very strategic for trade and service routes and is used as a connecting route between Malang and Surabaya. The pattern of settlements is formed around the square with the pattern following the grouping of a plural society. Most of the colonial buildings in Malang adhere to Dutch architecture. Colonial buildings built before the 1920s have an "Indische Empire" architectural style which is an old European model building. In the years after the 1920s the colonial building had an architectural style of "Nieuwe Bouwen" which had been adapted to the climate and building techniques of the Dutch East Indies. The existence of the Dutch colonial style building at this time can still be enjoyed by the facade of the building. Contextual buildings are designed based on the existing environmental and climate systems to realize buildings that adopt Dutch colonial architecture and the system of structuring the routes prioritizes users' comfort and safety when passing through these routes. The author uses the historical method which has four stages including heuristics, source criticism, interpretation and historiography. The purpose of writing this article is to find out the historical background of the architectural development of the Kayutangan area, Malang and to analyze the existence of Dutch colonial buildings in the Kayutangan area, Malang in 1900-2021.Sejarah kota Malang memiliki perjalanan yang cukup panjang hingga hadirnya kota Malang yang pesat seperti saat ini. Ditinjau dari sejarahnya, pada tahun 1914 kawasan Kayutangan hingga alun-alun kota Malang dijadikan sebagai pusat kota Malang pada saat itu. Hal ini dikarenakan letak geografis Kayutangan sangat strategis untuk jalur perdagangan dan jasa serta dijadikan sebagai jalur penghubung antara Malang dengan Surabaya. Pola pemukiman terbentuk di sekeliling alun-alun dengan polanya mengikuti pengelompokan masyarakat majemuk. Sebagian besar bangunan kolonial di Malang menganut arsitektur Belanda. Bangunan kolonial yang dibangun sebelum tahun 1920-an memiliki gaya arsitektur “Indische Empire” yang merupakan bangunan model Eropa lama. Pada tahun setelah 1920-an bangunan kolonial memiliki gaya arsitektur “Nieuwe Bouwen” yang telah disesuaikan dengan iklim dan teknik bangunan Hindia Belanda. Eksistensi bangunan gaya kolonial Belanda pada masa kini masih bisa dinikmati fasade bangunannya. Bangunan kontekstual yang dirancang berdasarkan sistem lingkungan dan iklim yang ada untuk mewujudkan bangunan yang mengadopsi arsitektur kolonial Belanda dan sistem penataan jalur-jalur lebih memprioritaskan para penggunanya nyaman dan aman ketika melewati jalur tersebut. Penulis menggunakan metode sejarah yang memiliki empat tahap diantaranya heuristik, kritik sumber, interpretasi dan historiografi. Tujuan penulisan artikel ini adalah untuk mengetahui latar historis perkembangan arsitektur kawasan Kayutangan, Malang serta untuk menganalisis eksistensi bangunan kolonial Belanda di kawasan Kayutangan, Malang pada tahun 1900-2021.